Solar cultivation of microalgae in a desert environment for the development of techno-functional feed ingredients for aquaculture in Qatar - Rihab Rasheed (14153385) (2022)
The demand for aquaculture feed will increase in the coming years in order to ensure food security for a growing global population. Microalgae represent a potential fish-feed ingredient; however, the feasibility of their sustainable production has great influence on its successful application. Geographical locations offering high light and temperature, such as Qatar, are ideal to cultivate microalgae with high productivities. For that, the environmental and biological interactions, including field and laboratory optimization, for solar production and application of two native microalgae, Picochlorum maculatum and Nannochloris atomus, were investigated as potential aquaculture feed ingredients. After validating pilot-scale outdoor cultivation, both strains were further investigated under simulated seasonal conditions using a thermal model to predict light and culture temperature cycles for the major climatic seasons in Qatar. Applied thermal and light variations ranged from 36 °C and 2049 μmol/m2/s in extreme summer, to as low as 15 °C and 1107 μmol/m2/s in winter, respectively. Biomass productivities of both strains varied significantly with maximum productivities of 32.9 ± 2.5 g/m2/d and 17.1 ± 0.8 g/m2/d found under moderate summer conditions for P. maculatum and N. atomus, respectively. These productivities were significantly reduced under both extreme summer, as well as winter conditions. To improve annual biomass productivities, the effect of implementation of a simple ground heat exchanger for thermal regulation of raceway ponds was also studied. Biomass productivities increased significantly, during extreme seasons due to respective cooling and heating of the culture. Both strains produced high amounts of proteins during winter, 54.5 ± 0.55% and 44 ± 2.25%, while lipid contents were high during summer reaching up to 29.6 ± 0.75 and 28.65 ± 0.65%, for P. maculatum and N. atomus respectively. Finally, using acute toxicity assay with zebra fish embryos, both strains showed no toxicity even at the highest concentrations tested, and is considered safe for use as feed ingredient and to the environment. Other Information Published in: Science of The Total Environment License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.scitotenv.2022.155538